(3JCOjH GdNjd hEUdGM eG aSO efgGs
(3ChdgG (B:s
(3GdMeO ddg QH GdYGdejf CeG HYO , aEfG bO QCjfG ef JYGde NUdI ai hbJg dG jcGO s
(3BNQgG (B:s
(3EPG cGfJ bUjQI hcGfJ YQjVI YhVJ Yf GdWhd hGddg CYde s
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B6 - (3U (B7 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B8 - (3U (B255s
(3agQS GdeNWhWGJ GdeUhQI (B((3eYgO GdeNWhWGJ GdYQHjI(B) - (3LRA (B4 - (3bSe eYGQa YGeg (B- (3U (B8 s
(3eUOQ GbJfGA GdCUd (B:s
(3CMeO GdKGdK (B/ (3GSJGfHhd (B(2114) s
Keywords: (3Gdafhf GdMQHjI h GdaQhSjIs